Risks of pelvic inflammatory disease and bacterial vaginosis in adenomyosis patients using levonorgestrel intrauterine device or oral norethindrone - Niu, Szu-Yun; Yi, Yu-Chiao; Shih, Yu-Hsiang; Tseng, Jenn-Jhy (Frontiers in Endocrinology, 2025)
BackgroundPatients with adenomyosis frequently experience menorrhagia and dysmenorrhea. Levonorgestrel-releasing intrauterine device (LNG-IUD) and oral norethindrone are widely used non-surgical treatment options. However, their associated risks of pelvic inflammatory disease (PID) and bacterial vaginosis (BV) have not been well reported in the previous studies.MethodsThis multi-institutional retrospective analysis was performed using de-identified electronic health records from the TriNetX Research Network. Patients with adenomyosis treated with LNG-IUD or oral norethindrone were identified. A 1:1 propensity score matching (PSM) was conducted to control for potential confounding variables. Subgroup analysis was performed to evaluate the outcomes of the patient group with hemoglobin (Hb) ≥10 g/dL or Hb <10 g/dL. Primary outcomes include risks of PID and BV. Secondary outcomes included risks of severe anemia (Hb < 10 g/dL), breast cancer, mood disorder, and cancer antigen 125 (CA-125) >35 U/mL.ResultsAfter PSM, the LNG-IUD group showed a significantly lower risk of PID (hazard ratio (HR) 0.545; 95% confidence interval (CI) 0.483–0.616) and Hb <10 g/dL (HR 0.850; 95% CI 0.775–0.932) compared with the oral norethindrone group. In contrast, the risk of BV was significantly higher in the LNG-IUD group (HR 1.223; 95% CI 1.116–1.342). No significant differences were observed between the two groups regarding associated breast cancer, mood disorder, or CA-125 ≥ 35 U/mL.ConclusionThis study demonstrated that in patients with adenomyosis, treatment with LNG-IUD, compared with oral norethindrone, was associated with a lower risk of PID and severe anemia (Hb < 10 g/dL) but a higher risk of BV.